2019
DOI: 10.3846/transport.2019.8629
|View full text |Cite
|
Sign up to set email alerts
|

Concept of an Integrated Mobile Application Aiding Electromobility

Abstract: Increasing acceptance of electromobility is an important step towards sustainable transportation. However, besides its obvious environmental and economic benefits, the technology of Electric Vehicles (EVs) still has some significant operational drawbacks (e.g. relatively short driving range, long recharging time). Advanced mobile applications supporting travellers’ decisions, improving predictability and reliability could play a key role in the promotion of a more widespread use of the technology. Mobile appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Interaction Platform [3,4,5,6] [ 12, 13] [8, 9, 10, 11] Travel behaviour [14,15,16,17,18,19,20] Concept [3,4,5,6,21,22,23,24] Transport (or mobility) is already not only an activity to move travelers from point A to B, travelers participate in the travel process more actively and act as a moving information collection and management points. Individuals have their consciousness and requirements [1], this is why transport or mobility should be provided as a service.…”
Section: Maas Smartphone Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Interaction Platform [3,4,5,6] [ 12, 13] [8, 9, 10, 11] Travel behaviour [14,15,16,17,18,19,20] Concept [3,4,5,6,21,22,23,24] Transport (or mobility) is already not only an activity to move travelers from point A to B, travelers participate in the travel process more actively and act as a moving information collection and management points. Individuals have their consciousness and requirements [1], this is why transport or mobility should be provided as a service.…”
Section: Maas Smartphone Applicationmentioning
confidence: 99%
“…Another category is about the information management of various mobility services, e.g., The concept of smartphone application regarding services of personalized parking [21], airport [22], electromobility [23], and AV based demand-responsive transport [24]. The relevant system architecture and operational functions are modelled with detailed input and output data groups.…”
Section: Maas Smartphone Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Skrúcaný et al [88] point out the diverse scope of effects of electromobility implementation in various countries, which depends, i.a., the share of Renewable Energy Sources (RES) in the total electric power production. In their research studies, Csiszár et al [89] indicated the limited travel range of electric vehicles and the small number of public charging stations. Macioszek [71] also takes note of the longer charging time of EV batteries compared to fuel tanking in the case of conventional vehicles.…”
mentioning
confidence: 99%